(untitled) (Third Sector Social Economic Review, 2020)
In recent years, trade protectionism has been increasing worldwide. Especially after the global financial crisis, nations have implemented preventive measures more frequently. The increasing worldwide trade wars exacerbated global uncertainty and affected financial markets. As the uncertainties in trade policies or the possibility of a trade war increased, capital started to escape from emerging markets to more developed nations, in other words to safer markets. This led to challenges for nations with foreign investment needs such as Turkey and exerted an upward pressure on the exchange rate. The present study aimed to empirically analyze the impact of policy uncertainty due to higher protectionism tendencies in trade on CDS. A trade policy uncertainty index was developed using Google Trend as a political uncertainty indicator. The correlation between the two series was analyzed with Johansen (1988) and Johansen/Juselius (1990) Cointegration Analysis, and then the direction of the correlation was determined with causality analysis based on the Vector Error Correction Model (VECM). Based on the study findings, it was determined that when global trade uncertainty increased worldwide, the risk of Turkey increased although Turkey was not a party to the uncertainty; and thus, it was difficult to attract further investments to Turkey.